Examining the impacts of behavioral factors on wireless village services among rural community in Malaysia - Bolong, Jusang; Mohamed Shaffril, Hayrol Azril; Omar, Siti Zobidah; Alby, Jeffrey Lawrence D'Silva; Sahharon, Hamisah (Human Resource Management Academic Research Society, 2016)
The main attempt of this study is to examine the impacts of behavioural factors on wireless village services among rural community in Malaysia. The study was quantitative in nature where a developed questionnaire was used as the main instrument in collecting the data. Via a multi stage cluster sampling, a total of 400 villagers from four districts in Malaysia have been selected as the respondents for the study. It can be confirmed that all of the behavioural factors studied have a positive and significant relationship with usage of wireless village services. A number of discussion have been highlighted and it is a hope that such discussion can act as a basis for interested parties in constructing concrete strategies to further narrowing the digital gap between the rural and urban communities in Malaysia.